1976
DOI: 10.1111/j.1471-0528.1976.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors Associated With Fetal Chromosomal Anomalies in Spontaneous Abortions

Abstract: Summary The effect is described of maternal factors on the proportion of fetal chromosomal anomalies in a series of 2620 spontaneous abortions, of which 992 specimens were karyotyped. Maternal age was the most important factor associated with a rise in the proportion abnormal, followed by Social Class I or II and the use of oral contraception before conception. The problem of extrapolating from the proportion abnormal to absolute incidence of anomalies is discussed. In the case of increasing maternal age, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…It has recently been shown that women whose husbands had azoospermia and who had received artificial insemination with donor semen (AID) had a significant decline in fecundity after the age of 35 years (51-53). The rate of spontaneous abortion also increases with maternal age (53), probably due to an increased frequency of chromosomal abnormalities (54,55). The percentage of fetuses with chromosomal anomalies is double in women over 40 in comparison to women under 20.…”
Section: Age and Fertilitymentioning
confidence: 88%
“…It has recently been shown that women whose husbands had azoospermia and who had received artificial insemination with donor semen (AID) had a significant decline in fecundity after the age of 35 years (51-53). The rate of spontaneous abortion also increases with maternal age (53), probably due to an increased frequency of chromosomal abnormalities (54,55). The percentage of fetuses with chromosomal anomalies is double in women over 40 in comparison to women under 20.…”
Section: Age and Fertilitymentioning
confidence: 88%
“…The effect seemed dose-dependent. Alberman et al [1976] also reported that smokers showed a higher, albeit not significantly higher, proportion of abortuses with normal chromosomes. This suggests that smoking affects the conceptus directly.…”
Section: Cigarette Smokingmentioning
confidence: 92%
“…However, even this insignificant increase was due to monosomy X and structural abnormalities, and not polyploidy as Carr [50] had reported. Alberman et al [53] observed 32% abnormalities in 524 prior users, compared to 26% in 428 controls. Dhardial et al [54] found differences of a similar, but again insignificant, magnitude.…”
Section: Numerical Chromosomal Abnormalitiesmentioning
confidence: 94%